Bioethics and the Holocaust A Comprehensive Study in How the Holocaust Continues to Shape the Ethics of Health, Medicine and Human Rights - Gallin, Stacy; Bedzow, Ira (The International Library of Bioethics,, 2022)
This open access book offers a framework for understanding how the Holocaust has shaped and continues to shape medical ethics, health policy, and questions related to human rights around the world. The field of bioethics continues to face questions of social and medical controversy that have their roots in the lessons of the Holocaust, such as debates over beginning-of-life and medical genetics, end-of-life matters such as medical aid in dying, the development of ethical codes and regulations to guide human subject research, and human rights abuses in vulnerable populations. As the only example of medically sanctioned genocide in history, and one that used medicine and science to fundamentally undermine human dignity and the moral foundation of society, the Holocaust provides an invaluable framework for exploring current issues in bioethics and society today. This book, therefore, is of great value to all current and future ethicists, medical practitioners and policymakers - as well aslaypeople.